Demographic Variables and Retail Choice Pattern amongst Urban Nigeria Consumers - Igwe, Sunny R; Chukwu, Godswill C (Journal of Asian Business Strategy, 2016)
The policy importance of demographic studies is yet to be fully tapped as changes in retail pattern in most cities are worth explaining. The study looked at the impact of consumer demographics variables on consumer store choice. The study analysed the difference between retail choice based on consumer sex, age, marital status, education, income amongst others. A sample of 435 consumers was randomly and clustered selected from four major commercial cities in Nigeria namely; Kano, Abuja, Lagos and Port Harcourt, while Pearson chi-square was adopted to test the hypotheses. Results indicated that there is no significant difference between retail pattern choice and sex, marital status and religion while there is a significant difference between store choice based on income, age, education and economic position of the consumer. It concluded that demographic has a great difference on the patronage and choice of retail outlet. It recommended the possibility of targeting and segmenting retail along demographic profile.